تحديد شدة ونسبة الإصابة المفردة والمختلطة بداء الأكريات ( Coccidiosis ) في مزارع دجاج اللحم في كل من محافظات اللاذقية وطرطوس وادلب (سورية) - نيصافي, علي (Latakia University Journal -Biological Sciences Series, 2019)
تكشف نتائج الدراسة الممتدة من عام (1999) حتى عام (2003) انتشار داء الأكريات في مزارع رعاية الفروج الذي ينتشر بكثافة ولكن بنسب متفاوتة وخاصة في المنطقة الساحلية ذات المناخ الأكثر ملاءمة لهذا المرض وبلغت نسبة الإصابة في كل من محافظة طرطوس واللاذقية وادلب (%85,28), (%83),(84,05) على التوالي وبلغ متوسط نسبة الإصابة (%84,28) في أعوام الدراسة الخمسة كما لوحظ ازياد نسبة الإصابة طردا مع زمن سنوات الدراسة وهذا يدعو إلى تطبيق الشروط الصحية الصارمة ودراسة فاعلية البرامج الوقائية السابقة واختبار فاعلية مضادات الأكريات المستخدمة منذ فترة طويلة وتطوير بدائل مضمونة وتظهر النتائج أن الإصابة المختلطة هي السائدة وقد بلغت (%62,30) في حين بلغت نسبة الإصابة المفردة(%37,70 ). تراوحت شدة أغلب الإصابات بين الدرجة الخفيفة (+) والدرجة المعتدلة (++) في المزارع التي شملها البحث فقد بلغت نسبة الإصابة بالأيميرية الأعورية تينيلا(%60,73) وتلتها الأيميرية ماكسيما(%41,88) فالأيميرية أسيرفولينا(%26,8) ثم الأيميرية برونيتي(%2,82). Based on the results of the study which lasted from1999 to 2003, it can be said that all poultry farms are infested with coccidiosis, which is intensely spread but in varying percentages, particularly in the coastal region. This is because it has the most suitable climate for this disease. Infestation percentage in the governorates of Tartous, Lattakia, and Idleb are (85.28%), (84.05%), and (83%), respectively. The average infestation percentage during the five years of study is (84.28%). It has also been noticed that infestation percentage increases with the 1 time of study, which calls for increasing austerity in implementing health conditions, studying the efficiency of previous prophylactic programs, testing the effectiveness of anti-coccidiosis drugs that are in use for a long time, and developing guaranteed substitutes. The results also demonstrated that the varying infection is common, where it reached (62.30%); whereas the rate of single infections reached (37.70 %). Severity of most cases ranged between mild (+) and moderate (++) in the governorates studied. Infestation rate with secal Eimeria tenella (%60,73) followed by E.maxima(%41,88),then E. acervulina (%26,8), then E.brunetti (%2,82).